A 3D Design System of Skirt Profile Based on OpenGL. (August 2020) - Xu, Jun; Wang, Xiaobo
Abstract: Personalized customization is inseparable from effective communication between designers and consumers, which is often aided by 3D software. Based on the OpenGL graphics interface, this paper studies and developed a three-dimensional interactive skirt design system. And This system can help designers and consumers quickly agree on the skirt profile and record the profile parameters. What's more, it can help designers design and produce clothes that are more in line with consumers' needs. The research process can be divided into four parts: the establishment of the skirt point cloud model, the triangular meshing of the point cloud model, the rendering of the triangular meshing model, and the development of the interactive interface. The design of skirt length, contour, and pleats can be parametric now with the realistic virtual visual effect. Therefore, this paper provides new ideas and methods for achieving the "what you see is what you get" skirt design concept.